Recent advances of engineering cell membranes for nanomedicine delivery across the blood–brain barrier - Shengnan Yuan; Dehong Hu; Duyang Gao; Christopher J. Butch; Yiqing Wang; Hairong Zheng; Zonghai Sheng (Journal of Nanobiotechnology)
Abstract The blood-brain barrier (BBB) poses a major challenge to the effective delivery of therapeutic agents for the treatment of central nervous system (CNS) disorders. The integration of cell membrane engineering with nanotechnology has recently enabled the development of membrane-engineered nanoparticles (CNPs). These nanocarriers exhibit enhanced BBB penetration and improved CNS targeting. This review systematically summarizes the latest advances in the development and application of CNPs, emphasizing how different cellular sources—such as erythrocytes, platelets, tumor cells, and leukocytes—impact delivery efficiency and therapeutic outcomes. We also examine the molecular mechanisms underlying nanoparticle-BBB interactions and highlight the importance of biosafety evaluations. Moreover, critical barriers to clinical translation, including large-scale manufacturing challenges, batch-to-batch variability, and regulatory complexities, are discussed. Finally, we explore emerging strategies—particularly the integration of artificial intelligence (AI)—that hold potential for overcoming existing clinical gaps, enabling the rational design and optimized development of CNP-based therapeutics for CNS disorders. By integrating mechanistic insights with translational perspectives, this review provides a clear conceptual and technological foundation for the development of next-generation CNS-targeted nanotherapeutics.